After the funeral and other stories eaudiobook - Hadley, Tessa (Books on Tape, 2023)
A masterful collection of stories that plumb the depths of everyday life to reveal the shifting tides and hidden undercurrents of ordinary relationships—Tessa Hadley is "one of the greatest stylists alive" (Ron Charles, Washington Post ). A Best Book of the Year: TIME, The New Yorker, The Washington Post , Vogue “Hadley is pure magic and After the Funeral is a triumph.”—Lily King, New York Times best-selling author of Writers & Lovers and Euphoria In each of these twelve stories, small events have huge consequences . Heloise’s father died in a car crash when she was a little girl; at a dinner party in her forties, she meets someone connected to that long-ago tragedy. Two estranged sisters cross paths at a posh hotel and pretend not to recognize each other. Janie’s bohemian mother plans to marry a man close to Janie’s own age—everything changes when an accident interrupts the wedding party. A daughter caring for her elderly mother during the pandemic becomes obsessed with the woman next door; in the wake of his best friend’s death, a man must reassess his affair with the friend’s wife. Cecilia, a teenager, wakes one morning in Florence on vacation with her parents and sees them for the first time through disenchanted eyes. As psychologically astute as they are emotionally rich, these stories illuminate the enduring conflicts between responsibility and freedom, power and desire, convention and subversion, reality and dreams. A vital addition to Tessa Hadley’s celebrated body of work, After the Funeral and Other Stories showcases what Colm Tóibín describes as "Tessa Hadley's extraordinary skill at making both surface life and deep interiors come fully alive."